2013
DOI: 10.5402/2013/485439
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis Infection among Pregnant Women in Jimma University Specialized Hospital, Southwest Ethiopia

Abstract: Background. Trichomonas vaginalis is a sexually transmitted parasitic protozoan known to be responsible for an estimated 180 million new infections per year, making it the most prevalent nonviral sexually transmitted pathogen worldwide. Method. A crosssectional study design was conducted on vaginal swabs by wet mount and Modified Columbia Agar culture technique in Jimma University Specialized Hospital (JUSH), ANC clinic, Jimma, Ethiopia. The study was done to assess the magnitude and associated risk factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
5
10
2
Order By: Relevance
“…These study results showed that there was a statistical correlation between trichomoniasis and vaginal discharge, burning sensation, and dyspareunia. This was in accordance with other studies in Nigeria [17], Aethiopia [18], Brazil [19], and Egypt [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These study results showed that there was a statistical correlation between trichomoniasis and vaginal discharge, burning sensation, and dyspareunia. This was in accordance with other studies in Nigeria [17], Aethiopia [18], Brazil [19], and Egypt [15].…”
Section: Discussionsupporting
confidence: 93%
“…It was found that there was a statistical correlation between the use of contraception method and trichomoniasis, and multivariate analysis revealed a statistical association with the use of IUD compared to both condom and hormonal methods. This was in accordance with ([ 18 , 20 ] [ 21 ], but others reported that hormonal contraception is strongly associated with trichomoniasis [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, symptoms such as vaginal discharge, vaginal itching and vulval ulceration were significantly associated with T. vaginalis infection. These findings were consistent with the results of previous studies in Ethiopia (Eshete et al, 2013). Additional symptoms such as pain during urination and pain during coitus have also been described to be associated with T. vaginalis (Fernando et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of T. vaginalis in this study was higher than many other studies elsewhere in Sub-Saharan Africa (Mairiga, 2011;Eshete, 2013;Lazenby et al, 2014). However, the prevalence was slightly lower than that reported by Iwueze et al (2014) in Anambra, Nigeria.…”
Section: Discussioncontrasting
confidence: 73%
“…Other risk factors for acquiring infection included having a lower level of education. 44,46 A study conducted by Eshete et al (2013) in pregnant women from Ethiopia showed that educational http://www.sajid.co.za Open Access status did play a critical role in respect to the increased number of T. vaginalis infections. 47 Mabaso et al (2020) found that abnormal vaginal discharge was associated with infection.…”
Section: Risk Factors For Infectionmentioning
confidence: 99%